Education Curriculum Management: A Case Study of Adolescents with Drug Dependence at Sentra Satria Baturaden - Ahmad Sauqi; Umi Arifah; Nurhidayah Nurhidayah; Agus Salim; Siti Fatimah (Journal of Educational Studies, 2025)
Narcotics, psychotropics, and other addictive substances are types of drugs or substances needed in the medical field. In handling them, victims of drug abuse can be treated with social service programs located in social rehabilitation centers. In their duties, social workers help provide assistance to victims related to using social services. The aim of this research is to analyze educational support through curriculum management for adolescents with narcotic dependence. This research uses a qualitative approach with a case study type. Data collection techniques consisted of observation, interviews, and documentation. Data analysis techniques used the Miles and Huberman and Saldana model, which includes data collection, data condensation, data display, and data verification. The research results show that the implementation of social rehabilitation for victims of drug abuse carried out at the "Satria" Center Baturraden includes: assessment, intervention, evaluation, and termination. Second, the supporting factors in the social rehabilitation process are: resident self-confidence, spiritual enthusiasm, therapy and guidance for residents, family atmosphere at "Satria" Center Baturraden, adequate facilities, a supportive environment, and peer support among residents. Meanwhile, the inhibiting factors are: insufficient family support, dishonesty during assessment, and delayed activities due to the Covid-19 pandemic.